Acridine-based dyes as high-performance near-infrared Raman reporter molecules for cell imaging. Issue 6 (25th January 2022) - Du, Jiasheng; Li, Jinming; Li, Yuzhan; Wang, Dong; Cao, Hui; He, Wanli; Zhou, Yang
Abstract : A surface-enhanced Raman scattering (SERS) nanoprobe has been proven to be a promising tool for near-infrared (NIR) biomedical imaging and diagnosis because of its high sensitivity and selectivity. Abstract : A surface-enhanced Raman scattering (SERS) nanoprobe has been proven to be a promising tool for near-infrared (NIR) biomedical imaging and diagnosis because of its high sensitivity and selectivity. However, the development of NIR SERS reporters has been a bottleneck impeding the preparation of ultrasensitive SERS probes. Herein, we report the design and synthesis of a series of SERS reporters in the NIR region based on 10-methylacridine (AD). The AD nanotags (gold nanostar–AD molecules–BSA, AuNS–AD–BSA) exhibit appreciable SERS signals and can be detected at as low as the sub-picomole level. The results of in vitro imaging experiments show that it can be used in live-cell delineation.